Adesão dos dependentes de drogas psicoativas ao tratamento em CAPSs AD - Reis, Larissa Ferraz [UNIFESP] (2016)
Faced with so many and different treatments for substance dependents, it was our interested to give voice to patients in Psychosocial Care Centers Alcohol and Drugs / CAPS ad in Sao Paulo. This qualitative research with 40 users intended to analyze the reasons that led them to begin, to remain or to abandon treatment. The three listed units by the municipal coordination of mental health are managed by social organizations. The first phase of the collection at the entrance, with interviews content analysis indicates heterogeneous socio-demographic profile. More than 50% of the sample had previous treatments. The main drugs were cocaine / crack and alcohol. Most participants declared to follow total abstinence, and some of them incorporated harm reduction. The results showed that the search for treatment was motivated by guilt, loss and desire to restore the dignity and self-respect. In this regard, these reasons should be better explored by the team, because, beyond verifying the relationship that the patients establish with the psychoactive substances, it’s important to unveil the meanings they attach to treatment and then, use more efficient therapeutic approaches. Many patients declared need for medication in order to relieve withdrawal symptoms or to create aversion to drugs. Besides, it was expressive family participation in treatment, which appears as a source of support and challenging. Most of the patients did not know clearly the dynamics of CAPS ad. Many of them have shown a tendency to transfer the responsibilities of the treatment, but others have had the expectation to participate more actively in their process and they hoped to take new paths with the support offered to them. Thus, one should pay attention to the demands that the patient brings and encourage their autonomy. In the initial call, impressions were good, but not enough to keep people in treatment. Through the analysis of medical records, it was found that only 4 subjects joined. These data indicate that other aspects of the adherence must be investigated, such as the shortcomings of the service and the culture of the subjects “do not point out errors / not inform. It Should be a priority the continuation or the beginning of new research aimed to study the treatment in the institutions to consider new interventions, especially for the first month of treatment, during which there was the largest drop, as well as more efficient care strategies throughout the process; Finally, it is necessary to strengthen both contact with the community in order to stimulate a dialogue that reduces stigma and prejudice, as well as relations with other services, such as hostels that despite being very present in the life of the respondent public, cannot hold the individuals for the necessary time for their recovery. The second stage, after three months, could not be assessed mainly due to lack of contact and also by the refusal of the subjects.